Sinc-Galerkin method for solving system of singular perturbed reaction-diffusion problems - Secer, Aydin; Onder, Ismail; Ozisik, Muslum (YILDIZ TECHNICAL UNIV, 2021)
In this paper, the system of singularly Perturbed Reaction-Diffusion problems which a re commonly used in physics and chemistry branches of science, were investigated. Sinc-Galerkin Method was used to obtaining the solution of problems. Because of there is no article about Sinc-Galerkin Method related to singularly perturbed Reaction-Diffusion problems in literature, the efficiency of the method was shown via this problem. There are important results that occurred after our research and application. Sinc Galerkin Method which was used in this paper as the main solution method gave better results according to parameter robust method and asymptotical initial value method. The figures and the tables show this competence and low errors.
Keywords: Sinc-Galerkin method; system of singularly perturbed reaction-diffusion problems; Engineering